2018
DOI: 10.1111/jzo.12581
|View full text |Cite
|
Sign up to set email alerts
|

Cast away: drift as the main determinant for larval survival in western fire salamanders (Salamandra salamandra) in headwater streams

Abstract: Unidirectional drift is amongst the most relevant population regulators in riverine animal populations. Drift occurs randomly, but it can also be a behavioural response to abiotic and biotic stressors, or the result of catastrophic events such as heavy rain. In this study, we investigate the spatiotemporal distribution of larvae of the fire salamander (Salamandra salamandra) in three headwater streams in the Eifel mountains, Western Germany. We marked 568 salamander larvae to conduct capture-recapture estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In contrast to the pueriparous populations, the density of water courses was one of the variables with the lowest contribution to explaining genetic differentiation in larviparous populations (Table 3). Unlike terrestrial-breeding amphibians, streams are expected to be relatively permeable to dispersal in aquatic amphibians, as they use streams (and other freshwater habitats) in all phases of their life cycle (Mims et al, 2015;Reinhardt, Bauldauf, Ilić, & Fink, 2018;Smith & Green, 2006 Note: The column "Type" denotes if a surface is continuous (C), categorical (CAT), or uniform (U), while the column "Transf" shows the data transformation applied to continuous layers (see Figure S7) or the resistance values assigned to binary categorical land use layers (A, absence of a specific land use; P, presence). Model performance was examined through the difference in the values of the AICc between the top ranked model and each tested model (ΔAICc).…”
Section: Does Reproductive Mode Influence Genetic Connectivity and mentioning
confidence: 99%
“…In contrast to the pueriparous populations, the density of water courses was one of the variables with the lowest contribution to explaining genetic differentiation in larviparous populations (Table 3). Unlike terrestrial-breeding amphibians, streams are expected to be relatively permeable to dispersal in aquatic amphibians, as they use streams (and other freshwater habitats) in all phases of their life cycle (Mims et al, 2015;Reinhardt, Bauldauf, Ilić, & Fink, 2018;Smith & Green, 2006 Note: The column "Type" denotes if a surface is continuous (C), categorical (CAT), or uniform (U), while the column "Transf" shows the data transformation applied to continuous layers (see Figure S7) or the resistance values assigned to binary categorical land use layers (A, absence of a specific land use; P, presence). Model performance was examined through the difference in the values of the AICc between the top ranked model and each tested model (ΔAICc).…”
Section: Does Reproductive Mode Influence Genetic Connectivity and mentioning
confidence: 99%
“…It is the only Central European amphibian species that deposits its offspring in lotic waters, predominantly in first and second order streams 15 , 16 . Due to the non-selective deposition of the larvae by the females 17 , the larvae are often drifted downstream 15 , 16 and accumulate in more lentic potholes 18 . However, European fire salamander larvae seem to lack morphological adaptations to their lotic environment, as known from other stream-dwelling salamanders 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Reinhardt et al 17 recently analyzed drift in the European fire salamander by tracking the spatial and temporal fate of individually marked larvae in three German first-order streams. While they confirmed the catastrophic effect of high summer precipitation as a trigger for larval drift, they could not find a significant evidence for random drift.…”
Section: Introductionmentioning
confidence: 99%
“…This larval stage, and the need of larviparous females to move into rivers (and other aquatic systems) to deposit offspring, likely create more opportunities for larviparous individuals to cross rivers. Both streams and rivers are associated with downstream larval drift in S. salamandra (Reinhardt et al, 2018;Veith et al, 2019) and the strong water current and drifting objects in both streams and rivers, together with the presence of predators, may cause high mortality rates (Segev and Blaustein, 2014;Reinhardt et al, 2018;Wagner et al, 2020). However, considering that only a relatively small number of immigrants are required to prevent population genetic differentiation due to genetic drift (Lowe and Allendorf, 2010), it is plausible that even a small proportion of successful dispersal events across rivers may minimize their barrier effects, even when re salamander populations often present high densities (and potentially large effective population sizes; Velo-Antón and .…”
Section: Discussionmentioning
confidence: 99%
“…In general, wider rivers exhibit stronger water currents and high water-ow velocities. The greater distance that salamanders must travel to successfully cross these rivers under these unsuitable aquatic conditions most likely hinder the swimming capacity of individuals, which eventually end up being dragged downstream and dying (Reinhardt et al, 2018). River width was also suggested as a determinant factor in shaping patterns of gene ow for an Amazonia frog (Adenomera andreae) by Fouquet et al, (2012) because the authors observed that populations of this species were more genetically differentiated in sections where the studied river was wider.…”
Section: Discussionmentioning
confidence: 99%